Hello Lexifer.

You have to equations

Y=4x-9 (eq1)

y= x-3 (eq2)

You know y because of (eq2) and so you substitute it in (eq1), this leads to

x-3 = 4x-9 (eq2 in eq1)

and you solve it for x.

Back to the two equations

Y=4x-9 (eq1)

y= x-3 (eq2)

You can use a substitution for x, too.

solving (eq2) for x

x = y+3 (eq2' )

and substitute it in (eq1) for x

4(y+3)-9=y (eq2 in eq1)

[In (eq1) you write y+3 instead of x because of eq2' ]

now you need to solve this equation for y

Still any questions? Then let us know

Yours

Rapha